(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: The lifestyle behaviors such as consumption of fruit and vegetables, along with time spent in physical activities and screen time are crucial for weight management, and improving these behaviors may be a key role in increasing mental health. This study aimed to investigate the role of lifestyle behaviors on depressive symptoms in children during the Covid-19 pandemic. Methods: This was a descriptive correlational study. The statistical population included male and female elementary school students (grades 4-6) in public schools in the eastern cities of Mazandaran province in 2020, among which 530 people were selected by random cluster sampling. Data collection tools included questionnaires of children's physical activity, fruit and vegetable consumption, children's depression, Screen time, and socioeconomic status. Data were analyzed using Mann-Whitney U, Kruskal-Wallis, Spearman correlation coefficient, and multiple linear regression tests. Results: The findings showed that just 13.3% of children had sufficient consumption of fruits and vegetables and 57.6% of students sufficient physical activity did not have.in addition, screen time was increased with age and be more in females. Regression analysis showed that the consumption of fruits and vegetables and physical activity both have the inverse effect on depressive symptoms, with the coefficient of effect -0.191 and -0.21 respectively; while screen time has a positive effect with an effective coefficient of 0.25 (Pvalue<0.05). Conclusion: It seems that in addition to physical activity and consumption of fruits and vegetables, the important role of Screen time in the design of interventions to promote mental health in children, especially during the outbreak of Covid-19 should be considered. Keywords: Depressive symptoms, Fruit and vegetable, Physical activity, Screen time, COVID-19.